(untitled) (DAPesquisa, 2021)
This article is based on the author’s master’s thesis about the presence of still lifes in contemporary art. Its purpose is to examine how still lifes in art history go beyond the chronology of time and mark their presence in contemporaneity. From a methodological approach based on bibliographic research and the iconographic study proposed by Georges Didi-Huberman, it presents a comparative analysis between images from different times through the following elements: persistence of motifs, persistence of forms, communication and news. So, it’s concluded that still lifes survive history and are adapted in contemporary art in a contesting and plural way, producing other meanings beyond the previous and conventional ones.